World Bank Research Digest, Vol. 14(1) - World Bank (World Bank, Washington, DC, 2019)
This issue focuses on Global Migration and features the following articles: Migration is Key for Reducing Poverty and Sustaining Economic Growth; How Labor Markets Fit Into the Global Migration Debate; How Big is the Payoff From Migration? Evidence from a Lottery; Reducing Barriers to Migration Boosts Welfare in China's Rural Villages; Exposure to Immigrant Classmates and Natives' Test Scores; Exposure to Immigrant Classmates and Natives' Test Scores; How Aging, Education, and Migration Affect Wages; Highly Skilled Migration: "Brain Drain" or "Brain Gain"? Aging, Trade, and Migration; Global Spillovers of National Migration Policies; and Getting a Better Sense of How Long Refugees Have Been in Exile; Creating a Migrant Rights Database.